2021
DOI: 10.1097/pap.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Flat/Invisible Dysplasia and Nonconventional Dysplastic Subtypes in Inflammatory Bowel Disease: A Review of Their Morphologic, Clinicopathologic, and Molecular Characteristics

Abstract: Patients with inflammatory bowel disease are at significantly increased risk of dysplasia and colorectal cancer (CRC). The early detection, histologic grading, and removal of dysplasia plays a critical role in preventing the development of CRC. With advances in endoscopic visualization and resection techniques, colectomy is no longer recommended to manage dysplasia, unless surveillance colonoscopy detects flat/invisible dysplasia (either highgrade dysplasia or multifocal low-grade dysplasia) or an endoscopical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 60 publications
0
29
0
2
Order By: Relevance
“…We previously reported detailed diagnostic criteria for each nonconventional subtype (Figures 2 and 3). [11][12][13][14][15][18][19][20] As described in our previous study, 12 all dysplastic lesions were rereviewed by at least one gastrointestinal pathologist (W.T.C. and G.Y.L.)…”
Section: H I S T O L O G I C C L a S S I F I C A T I O N A N D G R A ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported detailed diagnostic criteria for each nonconventional subtype (Figures 2 and 3). [11][12][13][14][15][18][19][20] As described in our previous study, 12 all dysplastic lesions were rereviewed by at least one gastrointestinal pathologist (W.T.C. and G.Y.L.)…”
Section: H I S T O L O G I C C L a S S I F I C A T I O N A N D G R A ...mentioning
confidence: 99%
“…6 More recently, our group and other investigators have reported that several different morphologic patterns of dysplasia, collectively known as nonconventional dysplasia, can occur in inflammatory bowel disease (IBD), which are characterized by unique clinicopathologic, molecular, and risk profiles compared with conventional dysplasia or sporadic adenomas. [11][12][13][14][15][16][17][18][19][20] There are seven subtypes: (i) hypermucinous dysplasia; (ii) goblet cell-deficient dysplasia; (iii) crypt cell dysplasia; (iv) dysplasia with increased Paneth cell differentiation (DPD); (v) sessile serrated lesion (SSL)like dysplasia; (vi) traditional serrated adenoma (TSA)-like dysplasia; and (vii) serrated dysplasia, not otherwise specified (NOS). Of these, hypermucinous, goblet cell-deficient, and crypt cell dysplasias appear to represent high-risk lesions, as they often present as flat/invisible lesions (~66%), show molecular features characteristic of advanced neoplasia (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…38 Detailed morphologic criteria for each nonconventional subtype have been previously published by our group (Figures 1 and 2). [29][30][31][32][33][34][35] Dysplasia found in the colectomy specimens was classified as undetected, only when there was no corresponding site of dysplasia detected and reported on previous colonoscopic biopsies. If dysplasia in the colectomy specimens was detected on prior colonoscopy, it was categorized as previously detected.…”
Section: Methodsmentioning
confidence: 99%
“…They appear to have distinct clinicopathologic and molecular features compared with conventional dysplasia or sporadic adenomas. [29][30][31][32][33][34][35][36][37] There are seven subtypes, including (i) hypermucinous dysplasia; (ii) goblet cell deficient dysplasia; (iii) crypt cell dysplasia; (iv) dysplasia with increased Paneth cell differentiation (DPD); (v) sessile serrated lesion (SSL)-like dysplasia; (vi) traditional serrated adenoma (TSA)-like dysplasia; and (vii) serrated dysplasia, not otherwise specified (NOS). Of these, hypermucinous, goblet cell deficient, and crypt cell variants have received the most attention, as they often present as flat/invisible dysplasia (~66%) and develop advanced neoplasia (40-93%) on follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation